Implementation of the Policy Support Instrument. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Within the terms of the proposed decisions, staff has formulated specific proposals on a number of issues raised in general terms during the previous Board discussion: (i) the modalities for a fixed schedule of reviews, including how to signal that a program is back on track; (ii) the application of a misreporting framework under the PSI; and (iii) the relationship between the PSI and the PRS process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Policy; Policy; PP; PSI; Support